Superior mesenteric artery blood flow in infants of very preterm and very low birthweight and its related factors - Evita Karianni Bermanshah Ifran; Wresti Indriatmi; Tetty Yuniarti; Nadjib Advani; Saleha Sungkar; Dewi Irawati Soeria Santoso; Rinawati Rohsiswatmo; Yvan Vandenplas; Badriul Hegar (Paediatrica Indonesiana, 2023)
Abstract Background Significant hemodynamic changes in preterm infants during early life could have consequences, especially on the intestinal blood flow. Alteration of superior mesenteric artery (SMA) blood flow may lead to impairment in gut function and feeding intolerance. Objectives To assess SMA blood flow velocity in very preterm and/or very low birth weight (VLBW) infants in early life and to elucidate the factors influencing them. Methods This is a cross-sectional study conducted in NICU at Cipto Mangunkusumo Hospital, Jakarta. Superior mesenteric artery (SMA) blood flow was evaluated by peak systolic velocity (PSV), end diastolic velocity (EDV), and resistive index (RI) measurement using Color Doppler US at < 48 hours after birth. Maternal and neonatal data that could be potentially associated with SMA blood flow were obtained. Bivariate analyses were conducted with a P value of < 0.05 considered significant. Results We examined 156 infants eligible for the study. PSV, EDV, and RI of SMA blood flow were not related to both gestational age and birth weight. Infant with small for gestational age (SGA) showed significantly lower EDV median [15.5 (range 0.0-32.8) vs 19.4 (range 0.0-113.0)] and higher RI [0.80 (range 0.58-1.00) vs 0.78 (range 0.50-1.00)] compared to appropriate for gestational age (AGA). Infants born from mother with preeclampsia showed lower PSV median [(78.2 (range 32.0-163.0) vs 89.7 (range 29.2-357.0)]) and EDV [16.2 (range 0.0-48.5) vs 19.4 (range 0.0-113.0)] compared to without PE, while absent/reverse end-diastolic velocity (AREDV) revealed a lower EDV median [16.9 (range 0.0 – 32.4) vs 19.4 (range 0.0 – 113.0)] compared to no AREDV. Furthermore, infants with hs-PDA showed lower EDV median [16.2 (range 0.0-113.0) vs 19.4 (range 0.0-71.1)] but higher RI median [0.80 (range 0.50-1.00) vs 0.78 (range 0.55-1.00)] compared to non hs-PDA. No difference in SMA blood flow across other factors was observed.